2022
DOI: 10.3390/genes13101774
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Single-Nucleotide Polymorphism in WNT4 Promoter Affects Its Transcription and Response to FSH in Chicken Follicles

Abstract: The signaling pathway of the wingless-type mouse mammary tumor virus integration site (Wnt) plays an important role in ovarian and follicular development. In our previous study, WNT4 was shown to be involved in the selection and development of chicken follicles by upregulating the expression of follicle-stimulating hormone receptors (FSHR), stimulating the proliferation of follicular granulosa cells, and increasing the secretion of steroidal hormones. FSH also stimulates the expression of WNT4. To further expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Ferroptosis is a newly discovered type of cell death that mainly depends on iron-mediated oxidative damage and subsequent cell membrane damage [ 56 ] and mainly manifests as glutathione (GSH) depletion and glutathione peroxidase 4 (GPX4) inactivation [ 57 , 58 ]. Previous research has shown that the TGF signaling pathway [ 59 ], Wnt signaling pathway [ 60 ], and cAMP pathway [ 61 ] are involved in the regulation of the follicle selection process in domestic chickens. Some studies have focused on ferroptosis induced by oxidative stress in the aquaculture industry and found that heat shock protein (HSP) , activating transcription factor 4 (ATF4) , solute carrier family 7 member 11 (SLC7A11), and GPX4 were associated with ferroptosis and the mitochondrial pathway [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a newly discovered type of cell death that mainly depends on iron-mediated oxidative damage and subsequent cell membrane damage [ 56 ] and mainly manifests as glutathione (GSH) depletion and glutathione peroxidase 4 (GPX4) inactivation [ 57 , 58 ]. Previous research has shown that the TGF signaling pathway [ 59 ], Wnt signaling pathway [ 60 ], and cAMP pathway [ 61 ] are involved in the regulation of the follicle selection process in domestic chickens. Some studies have focused on ferroptosis induced by oxidative stress in the aquaculture industry and found that heat shock protein (HSP) , activating transcription factor 4 (ATF4) , solute carrier family 7 member 11 (SLC7A11), and GPX4 were associated with ferroptosis and the mitochondrial pathway [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In sexually mature hens, one of the SYFs are selected to develop into hierarchical follicles daily or near‐daily, which initiates hierarchical development under the regulation of FSH (Wang et al, 2022; Zhong et al, 2022). Generally, there are 5–6 hierarchical follicles of increased sizes, i.e., F6/F5 to F1, and 8–13 SYFs in commercial hens (Álvarez & Hocking, 2012; Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on mammals demonstrated that MFN2 sustained the proliferation and differentiation of the granulosa cell by regulating its ATP production and metabolism (Feng et al, 2022;Liu et al, 2014). Herein, this study aimed to investigate whether Zhong et al, 2022). Generally, there are 5-6 hierarchical follicles of increased sizes, i.e., F6/F5 to F1, and 8-13 SYFs in commercial hens (Álvarez & Hocking, 2012;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%